2021
DOI: 10.3390/jcm10132860
|View full text |Cite
|
Sign up to set email alerts
|

Soluble C-Type Lectin-Like Receptor 2 Is a Biomarker for Disseminated Intravascular Coagulation

Abstract: Disseminated intravascular coagulation (DIC) is induced by excess activation coagulation, and activated platelets are also involved in pathogenesis. Therefore, plasma levels of soluble C-type lectin-like receptor 2 (sCLEC-2), a new marker for platelet activation, can be expected as a marker of DIC in critically ill patients. Plasma levels of sCLEC-2 and D-dimer were measured using the STACIA system. Plasma sCLEC-2 and D-dimer levels were significantly higher in patients with underlying diseases of DIC than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Therefore, large-scale studies are required to confirm the usefulness of this quick DIC score system for the diagnosis of DIC and pre-DIC. Regarding the survival of patients assessed using the quick DIC score system, approximately 50% of the patients diagnosed with possible DIC died, suggesting that the quick DIC score may predict poor outcomes as DIC patients still show poor outcomes and DIC is one of the most important causes of death in critical ill patients [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, large-scale studies are required to confirm the usefulness of this quick DIC score system for the diagnosis of DIC and pre-DIC. Regarding the survival of patients assessed using the quick DIC score system, approximately 50% of the patients diagnosed with possible DIC died, suggesting that the quick DIC score may predict poor outcomes as DIC patients still show poor outcomes and DIC is one of the most important causes of death in critical ill patients [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the mean plasma concentration of these soluble forms of CLEC-2 was 59-100 pg/mL in healthy volunteers and was increased to 260-380 pg/ml in patients with platelet-activating diseases 22 . In some patients with thrombotic microangiopathy or disseminated intravascular coagulation, the concentration of soluble CLEC-2 exceeds 1000 pg/ml [30][31][32] . Because platelets are retained in in amed glomerular capillaries 33 , the local concentration of soluble CLEC-2 may be higher in glomerular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 infection was diagnosed by polymerase chain reaction using the Gene expert system (Cepheid, CA, USA). We measured the plasma sCLEC-2 levels via chemiluminescent enzyme immunoassay (CLEIA) using previously described monoclonal antibodies and the STACIA CLEIA system (LSI Medience, Tokyo, Japan) [17,19]. In brief, magnetic particles were coated with the anti-CLEC-2 monoclonal antibody 11D5.…”
Section: Methodsmentioning
confidence: 99%
“…Soluble C-type lectin-like receptor 2 (sCLEC-2) has been introduced as a new biomarker of platelet activation [15]. Elevated plasma levels of sCLEC-2 have been reported in patients with thrombotic microangiopathy (TMA) and disseminated intravascular coagulation (DIC) [16,17], as well as in patients with acute coronary syndrome [18] or acute cerebral infarction [19].…”
Section: Introductionmentioning
confidence: 99%